METHODS OF DEVELOPING WRITING COMPETENCE WITH AUTHENTIC MATERIALS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In this article we examined the effectiveness of authentic materials in the writing classes and some authentic materials that can be used by language teachers to teach writing in the classroom. Also, the scientists’ studies of authentic materials used for teaching writing